URGENSI MANAJEMEN KONFLIK DALAM PENDIDIKAN ISLAM MULTIKULTURAL - Ansori; Nurasikin; Kasful Anwar (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2025)
Conflict is an inevitable dynamic within multicultural educational environments, including Islamic education. The diversity of cultural, religious, and ideological backgrounds in educational institutions creates a space for social interaction that is vulnerable to potential conflict. This study aims to explore effective conflict management strategies within the context of multicultural Islamic education by emphasizing Islamic values such as justice, deliberation (musyawarah), tolerance, and brotherhood (ukhuwah). The research method used is library research by analyzing various academic literatures and relevant documents. The findings indicate that conflict management in Islamic education must be comprehensive, encompassing preventive, interventive, and curative strategies. The approach should not only be technical, but also ethical and spiritual, where school principals and teachers play a central role as peace facilitators and cultivators of an inclusive school culture. This study recommends the integration of Islamic values and multiculturalism principles into educational policies and practices in order to foster a learning environment that is harmonious, just, and humane.